Alternative visions of learning: children’s learning experiences in the outdoors - Tony Rea (Educational Futures)
Outdoor learning opportunities for school pupils are likely to increase following the publication of the Government’s Manifesto for Outdoor Learning (DfES, 2005). However, the formalisation of outdoor education to meet local authority demands, and national policies and initiatives, presents the danger of outdoor education centres becoming increasingly similar to schools. This paper reports on interim findings from a doctoral research project investigating children’s learning experiences at a residential outdoor education centre. It suggests that the power of outdoor learning may lie in the informality and deeply contextual learning activities on these programmes. It argues for outdoor learning as an alternative vision of education that should be seen as essentially different from traditional schooling rather than an extension of schools. It argues for the freeing of outdoor education centres from the structural boundaries imposed by the national curriculum and government curriculum enhancement projects, whilst reducing or removing the demands for centres to continually investigate the impact of their work.